Efficacy of reduction therapy of natural human β-interferon and ribavirin in elderly patients with chronic hepatitis C, genotype 1b and high viral load - Arase, Yasuji; Kawamura, Yusuke; Suzuki, Yoshiyuki; Suzuki, Fumitaka; Akuta, Norio; Matsumoto, Naoki; Seko, Yuya; Sezaki, Hitomi; Kobayashi, Masahiro; Hosaka, Tetsuya; Hirakawa, Miharu; Saito, Satoshi; et al. (Hepatology research, 2012)
Aim:  To evaluate the efficacy of reduction therapy of natural human interferon (IFN)‐β and ribavirin in elderly patients with hepatitis C virus (HCV) genotype 1b and high viral load who had complications of anemia, low bodyweight (<50 kg), diabetes mellitus and/or hypertension. Methods:  Inclusion criteria were age of 65 years or older, HCV genotype 1b, and serum HCV RNA level of 5.0 logIU/mL or higher. A total of 23 subjects with hemoglobin level of less than 13 g/dL, low bodyweight, diabetes mellitus and/or hypertension were enrolled in this study (reduction‐dose group). IFN‐β was administrated i.v. at a dose of 6 million units daily for 4 weeks initially, followed by three times a week for 44 weeks. Ribavirin was given daily for 48 weeks at a decreased dose of one tablet per day compared to the ordinary dose described based on bodyweight. As a control, another 22 patients without anemia, low bodyweight and/or complications treated with the standard dose of ribavirin (standard‐dose group) were enrolled. Results:  Patients' rates with further dose reduction or discontinuation of treatment was 26.1% (6/23) in the reduction‐dose group and 77.3% (17/22) in the standard‐dose group. The sustained virological response (SVR) was 39.1% (9/23) in the reduction‐dose group and 27.3% (6/22) in the standard‐dose group (P = 0.404). Based on genetic variations near the IL28B gene (rs8099917), SVR was 44.1% (15/34) in patients with TT and 0% (0/11) in patients with TG (P = 0.008). Conclusion:  The reduction therapy of IFN‐β and ribavirin in elderly HCV patients with genotype 1b, high viral load, IL28B gene (rs8099917) of TT who had complications of anemia, low bodyweight, diabetes mellitus and/or hypertension is one possible selection of treatment.